Permaculture Design Tools for Climate Resilience - Milison, Andrew (Open textbook library., 2018)
Climate is also where we begin the design process in another tool referenced in the Permaculture design system. This is the Scale of Landscape Permanence, originated by P.A.Yeomans, the founder of Keyline™ Design. Yeomans asserts that the order of design is: Climate Landshape Water Supply Roads/Access Trees Structures Subdivision Fences Soil This book is predominantly about climate, and the macro influences of climate and climate change on design. As we get through the topics of climate analogues and climate change forecasting, we will end up moving down this list to see the climate’s influence on specific design choices.